T-cell Composition in Ileal and Colonic Creeping Fat – Separating Ileal from Colonic Crohn's Disease. (1st October 2018) - Kredel, Lea I; Jödicke, Lisa J; Scheffold, Alexander; Gröne, Jörn; Glauben, Rainer; Erben, Ulrike; Kühl, Anja A; Siegmund, Britta
Abstract: Background and Aims: Creeping fat [CF] is a hyperplasia of adipose tissue adjacent to inflamed intestine in Crohn's disease [CD]. Data from genome-wide association studies [GWAS] distinguished Crohn's colitis from ileal CD and ulcerative colitis [UC]. This study analysed the T-cell compartments of ileal and colonic mesenteric fat and corresponding mucosa to provide cellular proof for the suggested GWAS classification. Methods: Samples were obtained from 34 CD or UC patients. Cells were analysed by immunohistochemistry and flow cytometry, and tissue cytokine release was assessed by cytometric bead array. Results: Only ileal CF revealed the distinct adipocyte hyperplasia combined with dense T-cell infiltration and fibrosis; colonic fat from CD and UC patients lacked these findings. T-cell subpopulations differed between mesenteric fat in ileal CD, colonic CD and UC: ileal CF had nearly 10 times more T-cells than colonic fat. The proportions of regulatory and central memory T-cells were significantly higher in ileal CF compared with colonic fat in CD and UC. In all groups, the mucosal T-cell compartment was distinct from the mesenteric fat. Remarkably, correlation between disease activity and proportion of pro- and anti-inflammatory T-cell subpopulations was inverse, comparing ileal and colonic fat in CD. Conclusions: This first in-depth analysis of the T-cell compartment in ileal and colonic mesenteric adipose tissue in CD and UC identifies a unique T-cell niche in the ileal mesenteric fat tissue in CD. From a clinical point of view, our findings underscore the novel concept of colonic and ileal CD as distinct IBD entities.